지역 브랜드 쌀의 이화학적 특성 비교 - 최옥자(Ok Ja Choi); 장원용(Won Yong Jang); 송치영(Chi Young Song); 이미영(Mi Young Lee); 심기훈(Ki Hoon Shim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
The study examined and compared the physicochemical and characteristics of various rice brand varieties and private brand products on the market. The moisture content in the proximate composition of rice was 15.67~17.03%, crude protein content was 5.73~6.30%, crude lipid content was 0.38~0.95%, and crude ash content was 0.23~0.56 %. Ilmi and Ilpum had high moisture content, whereas Gosihikkari and Hopyeong had high crude protein content. In the Hunter's color value of rice flour, L value was 96.76~97.27, a value was -1.63~-0.63, and b value was 2.00~2.60. The WAI was 1.21~1.39, WSI was 0.63~0.93%, and amylose content was 14.63~20.86%, respectively; Gosihikkari and Ilmi showed the lowest values. The X-ray diffraction patterns of rice flours of all varieties showed an A shape. For the amylogram properties of rice flour, initial pasting temperature was $59.57{\sim}63.23^{°}C$, maximum viscosity was 569.00~718.67 B.U. (Brabender Units), breakdown was 303.00~423.67 B.U., and setback was 212.67~265.33 B.U.. For differential scanning calorimeter (DSC) of rice flour, onset temperature was $54.66{\sim}58.63^{°}C$, peak temperature was $65.87{\sim}68.14^{°}C$, end temperature was $73.37{\sim}75.54^{°}C$, and enthalpy was 1.98~2.95 cal/g. The rice varieties with high internal density and initial pasting temperature as well as low crude protein content, WAI, amylose content, and setback can be classified as good. Gosihikkari in Gyeonggi Province, Ilmi and Hopyeong in Jeollanam-do, and Samgwang in Chungcheongnam-do are among them. 본 연구는 시판되고 있는 경기도, 충청남도, 경상북도, 전라남도 등의 지역에서 시판되고 있는 브랜드 쌀 품종과 대형마트에서 판매하는 PB 제품의 이화학적 특성 및 호화 특성을 분석하여 비교 검토하였다. 쌀의 일반성분 분석에서 수분함량은 15.67~17.03%, 조단백 함량은 5.73~6.30%, 조지방 함량은 0.38~0.95% 그리고 조회분 함량은 0.23~0.56%로 나타났고, 전라남도 일미벼 품종과 경상북도 일품벼 품종의 수분 함량이 높았고, 경기도 고시히카리 품종과 전라남도 호평벼 품종의 조단백 함량이 낮았다. 쌀가루의 색도에서 L값은 96.76~97.27, a값은 -1.63~-0.63 그리고 b값은 2.00~2.60으로 나타났다. 쌀가루의 수분흡수지수는 1.21~1.39로 나타났고, 수분용해지수는 0.63~0.93%로 경기도 고시히카리 품종과 전라남도 일미벼 품종에서 낮게 나타났다. 쌀가루의 아밀로오스 함량은 14.63~20.86%로 경기도 고시히카리 품종과 전라남도 일미벼 품종에서 낮게 나타났다. 쌀가루의 X-선 회절도를 측정한 결과 모든 품종의 쌀가루는 A 도형을 나타냈다. 아밀로그램에 의한 쌀가루의 호화 특성 분석 결과, 호화개시온도는 $59.57{\sim}63.23^{°}C$, 최고점도는 569.00~718.67 B.U., 최고점도 시 온도는 $87.23{\sim}89.27^{°}C$, 최저점도는 264.67~295.00 B.U., $50^{°}C$로 냉각한 냉각점도는 418.33~563.33 B.U., 강하점도는 303.00~423.67 B.U. 그리고 치반점도는 212.67~265.33 B.U.로 나타났다. 시차열량주사계를 이용한 쌀가루의 호화엔탈피 측정 결과 호화개시온도는 $54.66{\sim}58.63^{°}C$, 호화정점온도는 $65.87{\sim}68.14^{°}C$, 호화종료온도는 $73.37{\sim}75.54^{°}C$ 그리고 호화엔탈피는 1.98~2.95 cal/g으로 나타났다. 내부치밀도와 호화 개시온도가 높고 수분흡수지수, 조단백 함량, 아밀로오스 함량 그리고 아밀로그램의 최종점도 및 치반점도가 낮으면 식미가 좋은 품종으로 봤을 때 경기도의 고시히카리 품종, 전라남도의 일미벼 품종 및 호평벼 품종 그리고 충청남도의 삼광벼 품종이 우수한 품종으로 나타났다.